The ecology of Sua pan and its flamingo populations - McCulloch, Graham (Trinity College (Dublin, Ireland). Department of Zoology, 2003)
Sua pan is part of the Makgadikgadi saltpan complex, which is derived from an ancient palaeo-lake that once covered much of present-day northern Botswana. Today it is the 'sump' of an endorheic drainage system, into which various inland rivers flow intermittently to form a shallow saline wetland. Sua pan is also well known as one of the most important breeding sites in southern Africa for Lesser (Phoeniconaias minor) and Greater Flamingos (Phoenicopterus ruber roseus) that migrate from all over southern Africa to breed. Because water in the pan is ephemeral numbers arriving and subsequent breeding success depends on the amount of flooding each year. Before the work described in this thesis, no detailed studies had been carried out on the limnology of this important wetland ecosystem. The aim of this research was to identify the main physical and chemical factors that control ecosystem functioning during two wet seasons and quantify the species, standing crop biomass and production of the main biological components in the food web. Greater and Lesser Flamingo population and breeding estimates were monitored and discussed in terms of food availability and 'good' breeding conditions. The amount of water input onto Sua pan was quantified by collating daily rainfall data from the river catchments and pan area, river discharge data from the inflowing rivers and potential evapotranspiration data. The area of flooding was determined from satellite images of the pan and flood periods were calculated from combined water input and daily evaporation rates. The largest estimated input of water varied between the basins on Sua pan and came mainly from direct rainfall, with Nata River discharge contributed almost 50% of the input onto the north basin. Groundwater input and output may also have had a large influence on the pans hydrological regime given the shorter predicted flood periods compared with observed flood periods, but its contribution is unknown. pH and conductivity were measured weekly in each basin over two wet seasons and ionic composition and nutrient concentrations were analysed from monthly samples of each basin and three inflowing rivers.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin